Application of Biology Learning Based on Local Wisdom Cibulan Tourism to Improve Students' Critical Thinking Skills - Wati Wati; Kartimi Kartimi; Asep Mulyani (Scientiae Educatia: Jurnal Pendidikan Sains, 2021)
Local culture-based learning is a form of learning that combines school with community culture. This study aims to examine the differences in critical thinking skills between students who apply and do not apply the learning of local wisdom science in Cibulan Tourism and the response of students who apply to learn local wisdom science Cibulan Tourism. This research was conducted in April 2019 at SMA Negeri 1 Jalaksana, Kuningan Regency. The population of all X classes in SMA Negeri 1 Jalaksana was 200. The sampling technique used is purposive sampling. The sample consisted of X MIPA 1 totaling 31 and X MIPA 5 totaling 31 students. Pretest-posttest control group research design with data collection techniques using observation, tests, questionnaires, and documentation. The results showed that the percentage of experimental class student activity was better than the control class, with a difference of 5.1% at the second meeting. The improvement in critical thinking skills shows an average N-gain of 0.57 for the experimental class and 0.15 for the control class. Percentage of questionnaire students strongly agree 19%, Agree 35% and do not know 45% while disagreeing and strongly disagree 0%. Research conclusions: There was an increase in student learning activities at each meeting between the classes that applied and did not apply local wisdom-based learning Cibulan tourism local wisdom. Students respond well to applying local wisdom-based learning Cibulan tourism on ecosystem material with a percentage reaching 69% and included in the strong category. Local culture-based learning can improve students' critical thinking skills.